Assessing the global impact of EU carbon pricing: Economic and climate spillovers - Elias Hasler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2025)
This paper explores the global economic and climate spillovers of the European Union Emissions Trading System (EU ETS), leveraging exogenous variations in carbon prices identified through a carbon policy surprise series. Findings reveal that higher EU carbon prices lead to significant and sustained reductions in greenhouse gas (GHG) emissions, both within the Euro Area (EA) and globally, with no evidence of carbon leakage. Structural Scenario Analysis confirms that these reductions are driven by energy efficiency improvements rather than solely by declines in industrial production. The results highlight the transmission of the shock trough the Brussels Effect, where EU carbon policies influence global standards, evidenced by stricter carbon policies abroad and shifts in investor behavior favoring green industries. Furthermore no region benefits economically from EU carbon pricing. Overall, the EU ETS proves effective in reducing emissions without being undermined by carbon leakage.
Keywords: E32; F42; F64; Q54; Q58; 330; Carbon Leakage; Spillovers; Carbon Pricing; Brussels Effect